2015
DOI: 10.1080/19388160.2015.1108888
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Motivations and Intentions of Potential Cruise Passengers from Different Demographic Groups: The Case of China

Abstract: The cruise industry is the fastest growing leisure market in the world. As an essential component, the cruise market in China is growing rapidly over the recent years with the introduction of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…Additionally, Fan et al (2015) compared motivation and intention of cruise passengers from different demographic profiles in China. They found that travelers from different demographic caliber differ in terms of their travel motivation.…”
Section: Demographic Factors and Travel Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Fan et al (2015) compared motivation and intention of cruise passengers from different demographic profiles in China. They found that travelers from different demographic caliber differ in terms of their travel motivation.…”
Section: Demographic Factors and Travel Motivationmentioning
confidence: 99%
“…However, these studies focused more on push and pull factors among youth travelers in Kenya (Njagi et al, 2017) and among travelers who traveled to Taiwan (Yung-Kun et al, 2015). Furthermore, the existing studies also looked at the relationships between sociodemographic factors and travel motivation among cruise passengers who traveled to China (Fan et al, 2015), those who traveled to national parks (Saayman and Saayman 2009) and those who traveled to sacred places for religious purposes (Irimias et al, 2016). From the reviewed literature, it is evident that sociodemographic factors are crucial in predicting travel patterns of tourists.…”
Section: Demographic Factors and Travel Motivationmentioning
confidence: 99%
“…Existing studies on the motivations of cruise ship tourists have a strong regional bias, focusing mainly on tourists from regions in which the cruise tourism industry is more developed (e.g., North America, the Mediterranean, the Caribbean, Northern Europe, Singapore, and Australia). Only a small number of studies consider emerging cruise travel markets (e.g., Fan et al, 2015 ; Lemmetyinen et al, 2016 ; Sun et al, 2018 ; Kawasaki and Lau, 2020 ). Extant studies have found that cruise tourists’ travel motivations vary by region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, for the selection of individual motivation factors and the questionnaire design, this article first uses a frequency analysis to categorize different cruise travel motivation indicators (as shown in Table 1 ) according to the existing literature and select the standard measurements with the highest frequency. Based on Prebensen et al (2013) , Fan et al (2015) , Lemmetyinen et al (2016) , and Sun et al (2018) , we further develop a theoretical construct in our research study. Social recognition, relaxation, enjoyment, self-esteem, discovery, socialization, and convenience and value are the key motivational factors within the theoretical construct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chinese students in Europe can be a great source of positive word-of-mouth promotion for a destination to attract more Chinese tourists if they themselves have good memories of their travel in Europe (Chen et al, 2015). The travel motivations of Chinese senior tourists must be clearly identified (Fan et al, 2015), as such identification helps market practitioners deliver satisfactory tourism products to their target market. Furthermore, Choi and Fong (2017) argue that Chinese seniors' travel preferences could be heterogeneous among different age cohorts.…”
Section: Discussionmentioning
confidence: 99%